2015
DOI: 10.4142/jvs.2015.16.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Tarantula cubensisextract alters the degree of apoptosis and mitosis in canine mammary adenocarcinomas

Abstract: In the present study, 13 clinical cases of canine mammary adenocarcinoma were evaluated in order to understand the effect of Tarantula cubensis extract (TCE) on tumor tissue. Punch biopsies were taken from the tumors before treatment with TCE. Subcutaneous injections of TCE were administered three times at weekly intervals (3 mL per dog). Between days 7 and 10 after the third injection, the tumor masses were extirpated by complete unilateral mastectomy. Pre- and post-treatment tumor tissues were immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
1
23
0
1
Order By: Relevance
“…Also it is used for the treatment of in mammary tumours in dogs (7). It was reported that Tarantula cubensis extract increased the apoptotic mechanism in mammary tumour cells (7,8). As it was reported by Gültiken and Vural (9) that Tarantula cubensis extract stopped the growth and reduced the size of the tumour similar clinical findings were observed in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Also it is used for the treatment of in mammary tumours in dogs (7). It was reported that Tarantula cubensis extract increased the apoptotic mechanism in mammary tumour cells (7,8). As it was reported by Gültiken and Vural (9) that Tarantula cubensis extract stopped the growth and reduced the size of the tumour similar clinical findings were observed in this study.…”
Section: Discussionsupporting
confidence: 90%
“…To explain the reason for the different levels of cytotoxicity between the normal and cancer cells, it was stated that the rapid metabolism rate of the cancer cells causes increased vulnerability against the extract. When Theranekron ® was tested on canine mammary tumors, immunohistochemical staining of these tumors revealed that Bcl-2 and Ki-67 expression levels were significantly affected after the Theranekron ® treatment [27]. Bcl-2 expression levels are crucial for apoptosis regulation, specifically for human breast cancer [28].…”
Section: Resultsmentioning
confidence: 99%
“…Due to a moderate improvement in the clinical condition and significant weight loss in such a short time, an experimental therapy was decided upon the consent of the owner. Theranecron (Tarantula cubensis extract) was introduced into the treatment based on the results of Guliken et al (2). The drug was injected subcutaneously once a week at a dose of 2.5 ml/dog.…”
Section: A Case Reportmentioning
confidence: 99%